Is the Performance of Shares in the Stock Market Affected by Monetary Policy Change and the Transmission Channel of Exchange Rate? - The Case of Turkey - Kudar, Alibey (Panoeconomicus, 2024)
In this study, in case that the objectives are price and financial stability, it is investigated whether the transmission channel based on exchange rate due to changes in monetary policy affects the performance of shares due to external debt stock. Borsa Istanbul is chosen as the stock market and the performance of nine sectors is examined during the high and low foreign exchange rate periods due to monetary policy change. The performance of the sectors is defined by portfolio performance measurement methods, and the TOPSIS (Technique for Order Preference by Similarity to Ideal Solution) analysis based on entropy is used for multi-criteria decision making. It is concluded that the monetary policy change affects the performance of the sectors, which constitutes a substantial proportion of external debt stock. JEL: C02, E44, E50, F31, G11.